2015 report on the health of Colorado's forests: 15 years of change - Duda, Joseph, author; Lockwood, Ryan, author; Mason, Lisa, author; Matthews, Susan, author; Mueller, Kim, author; West, Dan, author; Ciesla, William M., author; Colorado State Forest Service, publisher (Colorado State University. Libraries, 2016)
This year marks a milestone in tracking forest health and management in Colorado, with this publication representing the 15th annual report on the health of Colorado's forests. Throughout this period, we've witnessed many landscape level changes across Colorado. The forces and circumstances that have come together - climate and weather events, insects and diseases, wildfire and human impacts - have contributed to dramatic changes in the age and structure of our forests. And substantial growth is predicted in our wildland-urban interface, where human habitation intersects with natural vegetation and undeveloped land - an area currently only about 20 percent developed in Colorado. Increased development will make forest management even more challenging than in the past. The focus of these reports has varied over the years. Broader themes have included overarching topics such as forest stewardship and active management. Other, more focused reports provided readers with detailed descriptions of emerging and recurring threats, and specific forest types, such as high-elevation forests, lodgepole pine, aspen, ponderosa pine and urban and community forests. In this year's report, you will read about not only the current condition of our forests, but reflections on changes since the first report in 2001.
15 years of change
Report on the health of Colorado's forests
The reports describes "an annual investigation of critical forest health issues, including the identification of priority areas across the state where current forest conditions demand timely action." They are intended to "expand Coloradans' knowledge of and interest in our state's forest resources."
Reports produced by the Colorado State Forest Service in conjunction with Colorado Department of Natural Resources, Division of Forestry.
January 2016.
Keywords: forests and forestry; measurement; Colorado; forest health; forest management